CNOT6/6L-mediated mRNA degradation in ovarian granulosa cells is a key mechanism of gonadotropin-triggered follicle development - Xing-Xing Dai (Elsevier, 2021)
Summary: CCR4-NOT deadenylase is a major regulator of mRNA turnover. It contains two heterogeneous catalytic subunits CNOT7/8 and CNOT6/6L in vertebrates. The physiological function of each catalytic subunit is unclear due to the gene redundancy. In this study, Cnot6/6l double knockout mice are generated. Cnot6l−/− female mice are infertile, with poor ovarian responses to gonadotropins. Follicle-stimulating hormone (FSH) stimulates the transcription and translation of Cnot6 and Cnot6l in ovarian granulosa cells. CNOT6/6L function as key effectors of FSH in granulosa cells and trigger the clearance of specific transcripts in granulosa cells during preantral to antral follicle transition. These results demonstrate that FSH modulates granulosa cell function by stimulating selective translational activation and degradation of existing mRNAs, in addition to inducing de novo gene transcription. Meanwhile, this study provides in vivo evidence that CNOT6/6L-mediated mRNA deadenylation is dispensable in most somatic cell types, but is essential for female reproductive endocrine regulation.